2x+6y=16 show steps

4x+5y=11

2x+6y=16

2x=16-6y

x=8-3y

4(8-3y)+5y=11

32-12y+5y=11

-7y=-21

y=3

4x+5(3)=11

4x+15=11

4x=-4

x=-1

(-1,3)

4x+5y = 11 and 2x+6y = 16

Let’s start by solving 4x+5y = 11 for the variable x.

Move the 5y to the right hand side by subtracting 5y from both sides, like this:

From the left hand side:

5y - 5y = 0

The answer is 4x

From the right hand side:

The answer is 11-5y

Now, the equation reads:

4x = 11-5y

To isolate the x, we have to divide both sides of the equation by theother variables

around the x on the left side of the equation.

The last step is to divide both sides of the equation by 4 like this:

To divide x by 1

The x just gets copied along in the numerator. The answer is x4x ÷ 4 = x

To divide 11-5y by 4divide each term in 11-5y by 4 term by term. 11 ÷ 4 =**11/4**To divide y by 1

The y just gets copied along in the numerator. -5y ÷ 4 =The solution to your equation is:

x =Next, let’s solve 2x+6y = 16 for the variable y.

Move the 2x to the right hand side by subtracting 2x from both sides, like this:

From the left hand side:

2x - 2x = 0The answer is 6yFrom the right hand side:

The answer is 16-2x

Now, the equation reads:

6y = 16-2x

To isolate the y, we have to divide both sides of the equation by theother variables

around the y on the left side of the equation.

The last step is to divide both sides of the equation by 6 like this:

To divide y by 1The y just gets copied along in the numerator. The answer is y6y ÷ 6 = yTo divide 16-2x by 6divide each term in 16-2x by 6 term by term. 16 ÷ 6 =To divide x by 1The x just gets copied along in the numerator. -2x ÷ 6 =The solution to your equation is:

y =Now, plug the earlier result, x=11/4-5/4y, in for x everywhere it occurs in

y=8/3-1/3x.

This gives y=8/3-1/3(11/4-5/4y). Now all we have to do is solve this for y, to have our first solution.

8/3 evaluates to 1/3 evaluates to 11/4 evaluates to 5/4 evaluates to Multiply y andMultiply y and 1The y just gets copied along. The answer is yy5/4*y evaluates to 11/4-5/4*y evaluates to Multiply bywe multiply by each term in term by term. This is the distributive property of multiplication. Multiply and1 × =Multiply andMultiply 1 and yThe y just gets copied along. y × =1/3*(11/4-5/4*y) evaluates to - =The answer is8/3-1/3*(11/4-5/4*y) evaluates to Move the to the left hand side by subtracting from both sides, like this:

From the left hand side:

y - =The answer isFrom the right hand side:

- = 0The answer is

Now, the equation reads:

=

To isolate the y, we have to divide both sides of the equation by theother variables

around the y on the left side of the equation.

The last step is to divide both sides of the equation by like this:

To divide y by 1The y just gets copied along in the numerator. The answer is y ÷ = y ÷ = 3The solution to your equation is:

y = 3Lastly, to find the solution for x, we plug this answer for y into the earlier result that

x=11/4-5/4y.

This gives x=11/4-5/4(3). Now, simplify this.

11/4 evaluates to 5/4 evaluates to Multiply and 315/4*(3) evaluates to 11/4-5/4*(3) evaluates to -1x= -1So, the solutions to your equations are:

x= -1 and y= 3The answer is xThe answer is y